Experimento de campo com a assembleia de Oligochaeta no substrato artificial suspenso na coluna de água em três canais secundários da planície aluvial do alto rio Paraná. - Fernandes, Sue Ellen Prata (2010)
The aim of this study was to assess the Oligochaeta assemblage structure, along exposure period of artificial substrates, relating to some environmental variables, in Different channels of upper Paraná River alluvial plain. The samples for the study of Oligochaeta assemblage in artificial substrates were collected monthly from October 2006 to October 2007, in Baia River, and Ipoitã and Curutuba channels. The two axis of Principal Components Analysis explained 57,57% of data variability total so that the first component described seasonal variations in sampling stations. A total of 6.290 individuals were recorded, after the experiment, in a total of 24 taxa, belonging to families Opistocystidae, Enchytraeidae, Naididae and Tubificidae. The highest Oligochaeta densities were recorded in Baia River and the lowest in the Ipoitã channel. According to Detrended Correspondence Analysis (DCA) was observed separation of collection stations and hydrological periods. Correlations verified between the axes of PCA and DCA indicated to water chemical and physical variables influenced the Oligochaeta species composition and density between the channels and collection months. The results obtained in the current study evidenced that the colonization process in artificial substrate by Oligochaeta assemblage differed between hydrological periods and channels, with changes in species composition, density, abundance dominance and richness.